Photocatalytic Degradation of Microcystin-LR by Bismuth Tungstate - Zhang, Tingwen; Cao, Yanqiu; Gong, Aijun; Wang, Yujiao; Qiu, Lina (Asian Journal of Chemistry, 2014)
In this study, the photocatalytic degradation of microcystin-LR by bismuth tungstate (Bi2WO6) in simulated sunlight process was investigated. The effect of different parameters, such as light intensity, Bi2WO6 dosage, reaction temperature, pH and the initial concentration of microcystin-LR were discussed. The degradation rate increased with the increment of light intensity and temperature, due to the increase of number of active cites. The optimal pH was 1.20 and the degradation rate would reduced when the pH increased. Experiments showed that, the ratio of [Bi2WO6]/[microcystin-LR] was a constant quantity. Only when the ratio was increased, the degradation rate can be improved. The photocatalytic reaction was also found to follow pseudo-first-order kinetics. Moreover, experiments showed a promising result as for the recycling of Bi2WO6.